2011
DOI: 10.1111/j.1559-1816.2011.00848.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Identity Patterns in Culturally Diverse Organizations: The Role of Diversity Climate1

Abstract: Many of the problems associated with cultural diversity in organizations stem from individuals' tendencies to categorize their social environment into “us” and “them.” We present the results of a field study (N = 1111) showing that diversity climate—an organizational climate characterized by openness toward and appreciation of diversity—may be the key to reducing these problems. The results show that diversity climate is positively related to cultural identity for majority members, and to organizational identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(114 citation statements)
references
References 44 publications
(65 reference statements)
5
106
1
2
Order By: Relevance
“…Empirical studies have shown that the majority's attitude towards diversity is a strong predictor of minority members' sense of acceptance, and that a positive attitude is beneficial for intergroup contact (Hofhuis et al 2012;Tropp and Bianchi 2006;. Also, like any type of organizational change, implementing new diversity policies may cause resistance (Thomas and Plaut 2008).…”
Section: Importance Of Measuring Perceptions Towards Diversitymentioning
confidence: 99%
See 4 more Smart Citations
“…Empirical studies have shown that the majority's attitude towards diversity is a strong predictor of minority members' sense of acceptance, and that a positive attitude is beneficial for intergroup contact (Hofhuis et al 2012;Tropp and Bianchi 2006;. Also, like any type of organizational change, implementing new diversity policies may cause resistance (Thomas and Plaut 2008).…”
Section: Importance Of Measuring Perceptions Towards Diversitymentioning
confidence: 99%
“…These include two personality measures, Cultural Empathy and Emotional Stability which have been shown to affect employees' functioning in a multicultural context (Van der Zee and Van Oudenhoven 2000). Also, we will examine the relationship of the BTDS with diversity climate; a measure of the degree to which the organizational climate displays openness towards and appreciation of diversity (Hofhuis et al 2012;Luijters et al 2008).…”
Section: Present Researchmentioning
confidence: 99%
See 3 more Smart Citations